2016
DOI: 10.1002/jcu.22356
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of contrast‐enhanced ultrasonography over computed tomography for the detection of persistent type II endoleak after embolization: A case report

Abstract: The aim of this case report is to describe the use of contrast-enhanced ultrasonography in the detection of a type II endoleak after prior embolization with Onyx. A 74-year-old male patient with hypertension previously underwent endovascular repair of a 7.1-cm infrarenal aortic aneurysm. CT angiography surveillance revealed a type II endoleak associated with aneurysm sac expansion. Selective transarterial embolization of the endoleak was performed, but it was not possible to detect the persistent endoleak usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Similar to its advantage after TACE with iodized oil, CEUS often allows better detection of vascularity and thus endoleak in the presence of radiopaque material from prior endoleak embolization, such as ethylene vinyl alcohol (EVOH) copolymer (Onyx; Micro Therapeutics, Irvine, Calif), which can limit CT evaluation (78). A recent meta-analysis of studies comparing CEUS with contrast-enhanced CT showed that CEUS was equally sensitive in detecting type I, II, and III endoleaks and outperformed contrast-enhanced CT in overall sensitivity (79).…”
Section: Evaluation Of Endoleakmentioning
confidence: 99%
“…Similar to its advantage after TACE with iodized oil, CEUS often allows better detection of vascularity and thus endoleak in the presence of radiopaque material from prior endoleak embolization, such as ethylene vinyl alcohol (EVOH) copolymer (Onyx; Micro Therapeutics, Irvine, Calif), which can limit CT evaluation (78). A recent meta-analysis of studies comparing CEUS with contrast-enhanced CT showed that CEUS was equally sensitive in detecting type I, II, and III endoleaks and outperformed contrast-enhanced CT in overall sensitivity (79).…”
Section: Evaluation Of Endoleakmentioning
confidence: 99%
“…CEUS is reliable even with coils, plugs and glue. 26 Recently some authors 27 have suggested the use of four dimensional (4D) CEUS for follow up of fenestrated EVAR, which allows a reconstruction of the fenestrated endograft and its target vessels that is easier to interpret than CTA or 2D CEUS. Lowe et al 18 found the total number of endoleaks detected by standard CEUS and 3D CEUS was the same.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS has been shown to be as sensitive as CTA in detecting the type of endoleaks that would normally warrant an immediate intervention (types I and III) and can be more accurate in picking up slow endoleaks (type II) that CTA might miss or have difficulty detecting due to artefacts. [13][14][15] Minutes after contrast injection in CTA (the venous phase), the contrast density, within the aorta and an endoleak, is relatively low compared with the arterial phase. With CEUS, contrast resolution remains relatively high for a few minutes before significant depletion of contrast medium from cavitation or dissolution of microbubbles.…”
Section: Discussionmentioning
confidence: 99%